Early onset female pattern hair loss: A case–control study for analyzing clinical features and genetic variants. Issue 1 (April 2022) - Ohn, Jungyoon; Son, Ho-Young; Yu, Da-Ae; Kim, Min Su; Kwon, Sijin; Park, Won-Seok; Kim, Jong-Il; Kwon, Ohsang
Highlights: Female pattern hair loss (FPHL) is classified into two types: early and late onset. Early onset FPHL (eFPHL) patients are associated with androgen-related features. Single nucleotide polymorphisms around PPARGC1A were most significant for eFPHL. This study provided clinical and genetic features of eFPHL. Abstract: Background: Female pattern hair loss (FPHL), the most common cause of alopecia in adult women, is classified into two subtypes: early onset and late onset (or postmenopausal). Little is known about the clinical features and genetic characteristics of early onset female pattern hair loss (eFPHL). Objectives: To investigate the clinical features and genetic characteristics of eFPHL. Methods: Patients with eFPHL and controls without eFPHL were prospectively recruited. The demographic and clinical features were collected. Single nucleotide polymorphisms (SNPs) located around the selected 30 candidate genes potentially associated with eFPHL were evaluated. Results: eFPHL patients (n = 63) manifested a decreased hair shaft density and cross-sectional area of the hair shaft compared to the control group (n = 341). eFPHL is associated with androgen-related features, including scalp greasiness, folliculitis, hirsutism, and polycystic ovary syndrome. Scalp pain and itching have been reported more frequently in patients with eFPHL. Forty-nine SNPs located around PPARGC1A, ABCC4, CYP11B2, FSHB, and CYP19A1 were found to be significant for eFPHL, including two PPARGC1A -associated SNPs: rs186530605 and rs192713767 ( p  = 3.94 × 10 -11 ). Conclusions: This study provided clinical features and genetic variants for eFPHL, which could provide insight into the underlying pathologic etiology. Considering the limited number of patients, a large-scale study is required in the future.